Loistaa - Pieni Valo; Anttila, Pauliina; Jokelainen, Petteri; Kaltiainen, Katri; Mäkelä, Annika; Pylkkö, Veli-Matti; Åman, Christer; Åman, Riina ([Lauluyhtye Pieni Valo], 2013)
13 kappaletta.
Keywords: Pieni Valo : albumit